Plantas de cobertura e adubação nitrogenada como fonte de nitrogênio à cultura do milho em plantio direto - Cassol, Cidimar (2019)
The no tillage system (SPD) stands out as the predominant model used for grain production in southern Brazil. Thus, the use of cover crops become relevant to improve the quality of this system, providing protection of the so il and fixation/cycling of nutrients, especially nitrogen (N), with release for cultivation in succession. In this system, during the winter period, the predominant use of oats to obtain straw is highlighted. However, it is not the most adequate crop to pr ecede the maize crop, due to the high C N ratio that causes less N availability in the soil during decomposition. This work aims to evaluate the evaluate the equilibrium between residues of residues for soil protection and N release for the crop in success ion as a function of the Residual Quality Index (IQR) of winter cover systems, the productive capacity of maize over cover crop residues, with doses of N, during two agricultural crops, and the effect of cover systems on the increase of maize productivity after nine years of no till. The installation of no till was carried out in 2010 in the experimental area belonging to UTFPR, Campus Dois Vizinhos, under Red Latosol. The experimental design was of randomized blocks in subdivided plots with three replicate s. In the main plots were tested eig ht systems of winter cover (black oats, common vetch, forage turnip, white lupine, ryegrass, com mon ryegrass and oat+vet ch [O+V] and oat+vetch+turnip [O+V T ]) that preceded the corn crop. In the subplots, three nitrogen doses (0, 90 and 180 kg ha 1 ) were applied in maize crop cover. The A+E+N and A+ E consortium systems present the highest IQR with permanence of 2.7 Mg ha 1 of dry mass on the soil surface and release of 57 kg ha 1 of N The rate of release of nitrogen from the consortia is closer to the poaceae with amount of N released similar to that found for vetch. In the absence of mineral N the highest productive capacity of maize is verified in succession to vetch and lupine with 8.6 Mg ha 1 of grains, followed by consortia with productivity of 7.0 Mg ha 1 . With the addition of 90 kg ha 1 of N, the productive capacity of maize over all cover systems is equivalent to the highest dose used (180 kg ha 1 of N), with higher yields at 90 kg ha 1 t h e cultivation of corn on vetch , lupine and O+V+T with an average productivity of 10.2 Mg ha 1 . After nine years of no tillage management, the O+V+T and O+V systems presented an increased 2.5 and 1.5 Mg ha 1 in the production of DM and an increase of 37 k g ha 1 for both, in the a ccumulation of N in the tissues . The s ystems with vetch, lupine and O+V+T provided yield increases of 3.6, 3.2 and 2.5 Mg ha 1 , respectively, after nine years of no tillage to corn in the absence of N mineral. The systems with lupine, rye and A + E + N provide fertilizer maize with 180 kg ha 1 increase in yield of 1.1, 0.9 and 0.8 Mg ha 1 respectively in the same period.